Report on Discussion Forum on Information Services in the Asia-Pacific and AGRIS/CARIS in the 21st Century - An Asia-Pacific Regional Consultation - Ibach, M.; Byron, Y. (Center for International Forestry Research, 1997)
The information available to researchers in today’s world and the technology to access and utilise it is expanding rapidly. Unfortunately, most forestry and forestry research organisations in the Asia-Pacific region neither have access to nor can utilise effectively the vast amount of existing information for decision making. A number of organisations in the region share common objectives to develop capacity in the forestry research sector. To this end, representatives of the ASEAN Forest Tree Seed Centre (AFTSC) Project, ASEAN Institute of Forest Management (AIFM), Center for International Forestry Research (CIFOR), International Development Research Council (IDRC) and CAB International (CABI), and the Forestry Research Support Programme for Asia and the P acific (FORSPA) proposed solutions through collaborative activities. This report is the proceedings of the discussion forum on Information Services in the Asia-Pacific held at Bogor, Indonesia, from October 30 to 1 November 1996. The list of perceived needs generated by a preliminary survey guided the deliberations of the forum. Participants identified priority goals, action plans for their achievement and responsible agents/ agencies, expected time frames and likely costs. The Integrated Information System for the Agricultural Sciences and Technology (AGRIS) and the Current Agricultural Research Information System (CARIS) are part of the FAO’s larger network providing an extensive, worldwide database of information on research in agriculture and related issues. To address the issue of AGRIS/CARIS in the 21st century, an Asia-Pacific Regional Consultation was held in conjunction with the discussion forum. This report documents the discussions designed to enhance cooperative activities and develop new approaches to improve the coverage of forestry literature in AGRIS and for forestry research information in CARIS among the countries in the Asia-Pacific region; as well as review new developments in information technology and their impacts on information providers and users. A detailed, independent review was recommended to evaluate AGRIS and CARIS, and their future directions in the 21st century with special attention to the coverage of forestry information